Barriers and Facilitators to the Social Participation of Individuals Aging with a Long-Term Neurological Disability: A Scoping Review - Samuel Turcotte; Sirine Kheroua; Gloria Brun; Laura Gagnon; Nora Bustamante; Angéline Labbé; Pascale Simard; Megan Veilleux; Mia Lapointe; Manh Hung Nguyen; Mélanie Levasseur (Disabilities, 2025)
Supporting the social participation of individuals aging with long-term neurological disabilities is key to healthy aging. However, knowledge about the factors influencing their social participation remains limited and fragmented. Following the Joanna Briggs Institute methodology, this scoping review synthesized and integrated knowledge regarding the barriers and facilitators to the social participation of individuals aging with long-term neuro-disabilities. A search in four databases (MEDLINE, CINAHL, PsycInfo, and EMBASE) resulted in 18 studies involving 2587 participants with nine neurological conditions: stroke, multiple sclerosis, spinal cord injury, traumatic brain injury, aphasia, post-polio syndrome, spina bifida, cerebral palsy, and muscular dystrophy. A total of 38 barriers, 25 facilitators, and 4 factors with mixed influence to social participation were identified. Key reported barriers included the organic system (e.g., fatigue or pain) and macro environments (e.g., inaccessible built environment). The most common facilitators involved physical dimensions in personal factors (e.g., good physical functions) and micro-environments (e.g., supportive social environment). This review highlights the need for accessible infrastructure and community support to promote inclusivity and equity. Future research should focus on community-level factors and mixed study designs to provide robust evidence to improve social participation and healthy aging in this vulnerable population.